Advances in research and praxis in special education in Africa, Caribbean, and the Middle East - Mutua, Kagendo, 1966-; Sunal, Cynthia S. (Research on education in Africa, the Caribbean, and the Middle East., 2012)
This edited volume explores various issues pertaining to the education of children with disabilities in Africa, the Caribbean and Middle East. As a group, persons with disabilities have been subjected to social, cultural and educational exclusions of various forms and for various socially-scripted reasons. In education, for instance, individuals with disabilities have been altogether excluded from educational participation in many parts of the developing world or they have been excluded from pursuing meaningfully beneficial higher levels of education in developed countries like the United States. One of the social responses/remedies to the widely-acknowledged exclusionary practices experienced by learners with disabilities has been the widespread implementation of inclusive practices in the education of individuals with disabilities across countries, in the west and the developing regions of the world. A distinctive marker of difference in the way inclusive practices have been enacted in western countries versus those in the developing world has primarily stemmed from the fact that majority of western countries operate under funded mandates that also regulate the provision of education to persons with disabilities. While the ideal of inclusion has been highly desirable, many of countries in the developing world have floundered in their implementation due to lack sound legislative framework to guide implementation coupled with socio-cultural factors related to negative perceptions of disabilities and limited funding sources. Chapters in this volume explore inclusive education from a variety of perspectives.